A note on flag-transitive 3-(v, k, 2) designs
This article is a contribution to the study of the automorphism groups of 3-(v, k, 2) designs. Let S=(P,β) be a non-trivial 3-(q + 1, k, 2) design. If G acts flag-transitively on S